The Intention of Indonesian Muslims in Using Islamic Bank Based on Consumer Psychology Perspective - Awliya, Hanifah; Nurzaman, Mohamad Soleh (Journal of Strategic and Global Studies, 2020)
Islamic banking was born in Indonesia as a solution for the Indonesian Muslims to avoid the practice of interest in banking world. Seeing the number of Muslim which dominates by 82% in Indonesia while funding nominal of Islamic bank is still low when compared to conventional bank, through this research, the author raises the theme consumer psychology to analyze its influence on the intention of Indonesian Muslims to use Islamic bank funding product. Respondents in this research are Indonesian Muslims who are not customer of Islamic bank with a total of 450 respondents. Then the data collected was analyzed using Multiple Linear Regression model. The result shows that motivation, perception, learning, beliefe and attitude partially have an influence on the intention to use Islamic bank funding product, and then motivation, perception, learning, beliefe and attitude simultaneously have a significant influence on the intention to use Islamic bank funding product. The ability of independent variables in explaining dependent variable is equal to 69.7%. The conclusion of this research is in understanding banking consumer behavior, it can not only be seen from an economic perspective, but another perspective that needs to be directly targeted at feelings that will shape the patterns of consumer behavior, namely consumer psychology. Islamic banking must pay attention to consumer policies both in conducting products and in marketing their products. In addition, regulators also need to prioritize consumer psychology in policy making.